DEmiRNA-mRNA regulatory network reveals miR‐122-5p as a regulatory factor of arginine metabolism in necrotizing enterocolitis - Ding, Zhili; Guo, Ting; Tang, Qiang; Hong, Yaqiang; Lv, Zhibao; Lu, Li; Zhuang, Wenjun (Frontiers in Genetics, 2025)
ObjectiveNecrotizing enterocolitis (NEC) is a gastrointestinal emergency with relatively high morbidity and mortality in neonates. The role of microRNAs (miRNAs) in NEC is not yet entirely clear. This study aimed to explore the mechanism of miR-122-5p in NEC.MethodsDifferentially expressed (DE) miRNAs were sequenced in control and NEC mice. The DEmiRNA-mRNA regulatory network was constructed and the bioinformatics analysis was performed to identify the target mRNAs and potential roles of the DEmiRNAs. The miR-122-5p activation was explored in vitro in the human intestinal epithelial cell (FHs74Int) and rat intestinal epithelial cell (IEC-6). In vivo, mice were transinfected with miR-122-5p inhibitor before the NEC occurred. Mass spectrometry was used to qualify the concentrations of amino acids, and the viability of intestinal stem cell (ISC) was accessed to verify the biological function.ResultsPreliminarily, 15 miRNAs were found to be differentially expressed between NEC group and control group. Subsequent bioinformatics analysis revealed that miR-122-5p significantly contributes to the arginine metabolism in NEC through the DEmiRNA-mRNA regulatory network, with PRODH2 and ALDH18A1 being identified as its target genes. In vitro, miR-122-5p mimic inhibited the expression of PRODH2 and ALDH18A1 in the FHs74Int cells and IEC-6 cells. In vivo, inhibition of miR-122-5p led to increased expression of PRODH2 and ALDH18A1, along with elevated arginine levels. Following transfection with a miR-122-5p inhibiting adenovirus, the survival rate of NEC mice improved, and intestinal injury was alleviated.ConclusionMiR-122-5p inhibition could impact arginine metabolism by targeting PRODH2 and ALDH18A1, thereby mitigating intestinal injury in NEC.